2021
DOI: 10.1002/clc.23679
|View full text |Cite
|
Sign up to set email alerts
|

Defibrillation threshold of internal cardioversion prior to ablation predicts atrial fibrillation recurrence

Abstract: Background Many studies have reported the predictors of atrial fibrillation (AF) recurrence after persistent AF (peAF) ablation. However, the correlation between the atrial defibrillation threshold (DFT) for internal cardioversion (IC) and AF recurrence rate is unknown. Here we investigated the relationship between the DFT prior to catheter ablation for peAF and AF recurrence. Hypothesis DFT prior to ablation was the predictive factor for AF recurrence after peAF ablation. Methods From June 2016 to May 2019, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Intraoperative DC under complete left atrial and ventricular unloading by total cardiopulmonary bypass is a useful and effective method for selecting candidates for MAZE. Although few studies have investigated intraoperative DC before MAZE, several reports demonstrated that AF disappearance by DC before catheter ablation was a useful predictor of AF recurrence after catheter intervention [ 20 22 ]. Of our 12 patients who did not recover from intraoperative DC, we performed MAZE for 5 patients, even though NSR could not be restored by intraoperative DC because preoperative episodes of AF tachycardia were medically uncontrollable, and AF did not disappear in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative DC under complete left atrial and ventricular unloading by total cardiopulmonary bypass is a useful and effective method for selecting candidates for MAZE. Although few studies have investigated intraoperative DC before MAZE, several reports demonstrated that AF disappearance by DC before catheter ablation was a useful predictor of AF recurrence after catheter intervention [ 20 22 ]. Of our 12 patients who did not recover from intraoperative DC, we performed MAZE for 5 patients, even though NSR could not be restored by intraoperative DC because preoperative episodes of AF tachycardia were medically uncontrollable, and AF did not disappear in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our study [21] enrolled 82 consecutive patients (mean age, 65.0 ± 12.4 years), including 45 with persistent AF and 37 with long-standing persistent AF. The recurrence rate after ablation was high among patients with long-standing persistent AF.…”
Section: Af Durationmentioning
confidence: 99%